The Gambia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper assesses the macrofinancial linkages in The Gambia. Significant macrofinancial linkages persist in The Gambia, first and foremost between the public sector and the banks. Banks are highly exposed to the government through large holdings of short-term government debt, which is a legacy of the large financing needs of the previous administration. In addition, large claims have built up between government and state-owned enterprises (SOEs) on the one hand, and banks and the corporate sector including SOEs on the other. There has been persistent financial distress within the SOE cluster. Weak SOE performance has also led to arrears both to central government and within the SOE cluster.